Perancangan Antarmuka Pengguna Sistem Informasi Manajemen Sarana dan Prasarana di SMK Negeri 2 Singosari menggunakan Pendekatan Human-Centered Design (HCD) - Moh. Firnas Amrozi; Retno Indah Rokhmawati; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
This research was conducted based on the condition of the object of research that does not have a system to do the borrowing and return of the goods, the study was conducted at SMK Negeri 2 Singosari. Based on the problems that the researcher makes the interface design of information systems management infrastructure to manage the lending and return of goods. The interface design of information systems management infrastructure using the method of HCD (Human Centered Design) which is useful to design user interface design focuses on the needs of the user. This study resulted in a prototype that is used for 2 users that team facilities and infrastructure as well as teachers, are the main feature on this information system is borrowing and the return of the goods. This study uses a testing Usability Testing with assessment of the System Usability Scale (SUS) that focuses to mengihitung the level of Usability of the System. The end result SUS has a total value of 77 from around the user so that it can categorized the design of this system can be accepted by the user.(acceptable).